Detection of Urban Growth in Taiz City, Yemen, Between 1981 and 2022 by Using Google Earth™ and Geographical Information System Data - Aziz, Ahmed Abdul; Abdullah, Anwar; Isnain, Zulherry (Geological Agency, 2024)
Rapid urbanization brought serious socio-economic and environmental problems in many cities around the world, particularly in developing countries like Yemen. Urban